Costs of testing sick children in primary care with pulse oximetry: Evidence from four countries, both with and without electronic clinical decision support. - Susan Horton; Ulrich Adombi; Fenella Beynon; Mira Emmanuel-Fabula; Tara Herrick; Sandeep Kumar; Suzan Makawia; Mercy Mugo; Michael Onah; Michael Ruffo; Shally Awasthi; Maymouna Ba; et al. (PLOS Global Public Health)
Introducing pulse oximeters (PO) at primary care facilities can help health workers identify severely ill children who need referral to hospital thereby allowing for improved child clinical outcomes. Adding clinical decision support algorithms (CDSA) can improve adherence to Integrated Management of Childhood Illness guidelines. The current study analyses the costs of introducing PO either with or without an electronic CDSA using an RCT in India and Tanzania and in a pre-post design with an electronic CDSA in Kenya and Senegal. The impact of the intervention is discussed for the RCT (trial registration NCT04910750) and for the pre-post study (trial registration NCT05065320), following SPIRIT guidelines. Economic data were collected in all four countries using questionnaires administered at primary health facilities and referral hospitals and supplemented by information from administrative sources, following CHEERS guidelines. Trained research assistants at the facilities collected data on children enrolled and health outcomes. Net costs per 100 children managed using PO ranged from $16.62 (Kenya, health center) to $70.51 (Tanzania, dispensary), in both cases using CDSA. Senegal was an outlier at $385.45, using PO and CDSA in the smaller postes de santé. Major causes explaining variation included training modality, numbers of sick children attending the facility, and the effect of PO and CDSA on use of antibiotics, diagnostics, and hospitalizations. Standard care (without PO) was associated with fewer severe complications (primarily untimely hospitalizations), at lower cost, in the two countries where effectiveness data are available, India and Tanzania. Scaling up PO use at primary care level nationally could have an important budgetary impact. Findings suggest ways that costs could potentially be reduced. However, hospitalization costs borne by households may affect both household and provider behavior and limit the potential clinical benefits of pulse oximetry.